Parental competences and child resilience in the context of displacement in Colombia (2018)
This paper presents results of a research that arose from the interest of studying the phenomenon of forced displacement as an adversity, which can be overcome because human beings have the competences to mitigate psychosocial damages after living a shocking situation. The study aimed to establish relationships between the competences of fathers and mothers, the support they seek in the community and resilience factors in infants exposed to the armed conflict in a region of the Colombian Caribbean. Through a quantitative - correlative methodology, scales and inventories were applied to 230 families. The results showed a positive relationship between community integration and the ability of parental figures to guide infants. A positive relationship was found between the capacity of the parental figures to plan free time and the ability of children to understand the feelings and ideas of others. These results suggest lines of action in social programs aimed at strengthening family resources, achieving the difficult reparation of the victims and finding the desired national reconciliation in moments of post-agreement. © 2018 Fundacion para la Investigacion Social Avanzada. All rights reserved.